Nilai-Nilai Pendidikan Sosial dalam Perspektif Ibnu Khaldun - Karumiadri, Muh; Maksum, Muh. Nur Rochim; Ali, Muhammad (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
One of the well-known Muslim figures in the world of social education is Ibn Khaldun. The muqoddimah book is a monumental work by Ibn Khaldun that amazed Western thinkers. The purpose of this research is to deal with the crisis of students' social values in socializing, so that sometimes they have difficulty controlling emotions and there is the harsh treatment between them and even older people. The method used by the researcher is a literature study method. The results of this study are: 1) Social Education in Ibn Khaldun's perspective is education that is based on life in a society which is a place for students to live and participate in it, by applying the knowledge they have acquired at school or outside of school. 2) The values of social education in the perspective of Ibn Khaldun that can be taken from the history of civilized society in his muqoddimah book are the value of brotherhood, the value of simplicity and religious values. By instilling and applying the values of brotherhood, simplicity and religion, students will live in a society with full solidarity, namely helping each other, being able to control emotions so that they no longer dare to be rude to their peers even to older people, so that they are able to participate. in building a peaceful life in the community.